How does green innovation determine corporate physical investment? New empirical evidence - Chen, Sisi; Farooq, Umar; Tabash, Mosab I.; Alam, Mohammad Mahtab; Khudoykulov, Khurshid (Technological and Economic Development of Economy, 2025)
Due to the escalating issue of global warming and other environmental concerns, green innovation has garnered significant attention. However, there is a dearth of literature addressing the impact of green innovation on industrial investment. Therefore, the present study aims to investigate how green innovation affects corporate physical investment. We utilize a wide array of financial data from a panel comprising 11 Asian economies and employ the system GMM (generalized method of moments) to test the underlying hypothesis. The empirical findings reveal a positive and statistically significant effect of all proxies for green innovation, including patent registrations, the development of environmental technologies, innovation intensity, and green growth innovation, on corporate physical investment. The empirical analysis yields a crucial policy implication, emphasizing the importance of prioritizing green innovation and the adoption of modern technology. These initiatives not only boost investment volumes but also contribute to achieving environmental sustainability. By exploring the intricate relationship between green innovation and corporate physical investment, the current study introduces innovative insights to the literature on financial and environmental economics. First published online 03 September 2025